Prevalence of Frailty and Its Association with Hospital Outcomes in Elderly Patients: A Prospective Cohort Study (Cuestiones de Fisioterapia, 2021)
Frailty is increasingly recognized as a major geriatric syndrome characterized by diminished physiological reserve, reduced resilience to stressors, and an increased susceptibility to adverse health outcomes. As populations age worldwide, frailty has emerged as an important determinant of healthcare utilization, morbidity, and mortality among older adults, particularly those requiring hospitalization. Hospitalized elderly patients often present with multiple chronic illnesses, polypharmacy, cognitive impairment, nutritional deficiencies, and functional limitations, all of which may contribute to the development and progression of frailty. Consequently, frail individuals are less able to cope with acute medical conditions and are at greater risk of complications during and after hospitalization. Early identification of frailty has therefore become an important component of comprehensive geriatric assessment, enabling clinicians to stratify risk, individualize treatment plans, and allocate healthcare resources more effectively. The present prospective cohort study was conducted to determine the prevalence of frailty among hospitalized patients aged 65 years and older and to evaluate its association with important hospital-related outcomes. A total of 200 elderly patients admitted to the hospital were assessed for frailty using a validated frailty assessment instrument, such as the Clinical Frailty Scale or Fried Frailty Phenotype, and were subsequently followed throughout their hospital stay and for 30 days after discharge. The study evaluated several clinically relevant outcomes, including in-hospital mortality, prolonged length of hospital stay, 30-day readmission, and functional decline. The findings demonstrated that frailty was highly prevalent among hospitalized older adults, indicating that a substantial proportion of elderly inpatients possess reduced physiological reserves and increased vulnerability to health stressors. Furthermore, frailty was found to be independently associated with a significantly greater risk of adverse outcomes. Frail patients experienced higher rates of in-hospital mortality, longer hospital stays, increased likelihood of readmission within 30 days, and greater functional deterioration compared with their non-frail counterparts. These associations remained significant after adjustment for potential confounding factors, suggesting that frailty itself serves as an important predictor of clinical outcomes independent of age and comorbidity burden. The results highlight the value of frailty assessment as a practical and effective tool for identifying high-risk elderly patients who may benefit from targeted interventions, multidisciplinary management, early rehabilitation, nutritional support, medication optimization, and comprehensive geriatric care. Routine frailty screening at the time of hospital admission may facilitate timely risk stratification, improve clinical decision-making, enhance patient-centered care, and ultimately reduce adverse outcomes among older adults. Overall, the study underscores the importance of integrating frailty assessment into routine hospital practice and supports the development of frailty-attuned healthcare strategies aimed at improving outcomes and quality of life in the growing elderly population.